Citizenship Education and Current Educational Reform - Sears, Alan; Hughes, Andrew (Canadian Journal of Education/Revue canadienne de l’éducation, 1996)
This article examines the character of citizenship education in Canada as it is represented in the official policy documents of the provinces and territories, as opposed to the actual classroom practice of the curriculum-in-use. We consider policies in light of a typology of citizenship ranging from elitist to activist, and identify common as well as particular features of citizenship education. We find that the official curriculum of educational policy inclines towards an activist conception of citizenship. Cet article compare la formation en civisme au Canada, telle qu’elle se dégage des documents de politiques officielles des provinces et des territoires, aux cours de civisme dispensés dans les classes elles-mêmes. Les auteurs analysent les politiques à l’aide d’une typologie du civisme allant de l’élitisme à l’activisme et identifient les caractéristiques communes et distinctes de la formation en civisme. Selon les auteurs, les programmes officiels en la matière tendent plutôt vers une conception activiste du civisme.